PROBABILITY OF FAILURE ANALYSIS USING POINT ESTIMATE METHOD AND MONTE CARLO METHOD ON HIGHWALL SLOPES LOM DESIGN OF PIT EAST PT BERAU COAL - DAMAR SEGORO (NIM : 12113080), KRESHNA
Stability of mining slopes is one of the most important things to support mining activities. If the slope is not safe and failure occurs then it will be able to cause loss of material and even fatality. However, under conditions that are very far from the ideal word, it finds a lot of precision. Therefore, the probabilistic method provides a more systematic and quantitative way in the slope stability sequence so that information will be obtained (opportunities) of a slope for lumbarness. Based on the results of research using the Point Estimate Method and Monte Carlo method by using three cross sections, this research found that the cross section which has the largest probability of failure value is cross section A located on the western part of Pit East. And the value of safety factor of slope will continue to decrease while the value of probability of failure is getting bigger as the increase of slope height and the slope angle. In addition, using this probabilistic method can analyze the standard of safety factor from PT Berau Coal and provide recommended slope geometry according to acceptable probability of failure values.